2023
DOI: 10.3389/fmicb.2023.982422
|View full text |Cite
|
Sign up to set email alerts
|

First characterization of cultivable extremophile Chroococcidiopsis isolates from a solar panel

Abstract: IntroductionMicroorganisms colonize a wide range of natural and artificial environments. Even though most of them are unculturable in laboratory conditions, some ecosystems are ideal niches for bioprospecting extremophiles with unique properties. Up today, there are few reports concerning microbial communities found on solar panels, a widespread, artificial, extreme habitat. Microorganisms found in this habitat belong to drought-, heat- and radiation-adapted genera, including fungi, bacteria, and cyanobacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 84 publications
(93 reference statements)
0
5
0
Order By: Relevance
“…Solar panel samples were collected during the summertime of 2013 and 2014 for screening cyanobacteria and microalgae. The first isolation was made in Castenholz-D medium (Baldanta et al, 2023) and afterwards, microalgae and cyanobacteria were maintained growing on BG11. At this time, a consortium among microorganisms, bacteria and cyanobacteria/microalgae, was evident on BG11 plates.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Solar panel samples were collected during the summertime of 2013 and 2014 for screening cyanobacteria and microalgae. The first isolation was made in Castenholz-D medium (Baldanta et al, 2023) and afterwards, microalgae and cyanobacteria were maintained growing on BG11. At this time, a consortium among microorganisms, bacteria and cyanobacteria/microalgae, was evident on BG11 plates.…”
Section: Resultsmentioning
confidence: 99%
“…At this time, a consortium among microorganisms, bacteria and cyanobacteria/microalgae, was evident on BG11 plates. After several streaks, different strains were isolated (Baldanta et al, 2023). One of these strains, a unicellular green microalga, named D14, was identified by PCR 18S rRNA amplification reaching a homology of 99% with other Coelastrella strains.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It can be genetically engineered to withstand biofuels and ethanol ( 23 , 24 ) and was also able to produce hydrogen when immobilized in alginate beads ( 25 ). The third choice is Chroococcidiopsis cubana PCC 7433 (SAG39.79), which was first isolated from a dried pool in Cuba and is part of a genus that has extremophilic features, e.g., desiccation- and radiation-resistance ( 26 29 ). As an example, Fagliarone et al demonstrated that members of this genus were able to survive air-dried storage for 4 years ( 26 ).…”
Section: Introductionmentioning
confidence: 99%